Development strategies and foreign aid policies for low income countries in the 1990s - Ulrich Hiemenz (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
Most low income countries are characterised by a high dependence on exports of a small number of agricultural or mineral commodities. In the 1980s, the economic and social performance of these countries has been extremely dismal. Declining per capita incomes, stagnating food production, and an increasing foreign debt burden indicate a failure of development strategies applied in these countries as well as of foreign aid policies pursued by donor countries and institutions. Low income countries have suffered from a combination of adverse commodity price movements and an increasing inability to adjust to a changing external environment. Adjustment has been hampered by conflicting and often misguided policy signals, weak economic institutions, and a rapid deterioration of public management in general. These shortcomings were rooted in fundamental social conflicts, in particular the "personal rule" of parasitic elites or the emergence of a non-productive state class. A development strategy for the 1990s has to pave the way towards economic diversification and a better integration of domestic markets in low income countries. Such a strategy requires the discrimination of the commodity producing sector to be abandoned, a return to macro-economic stability, and institution building. Necessary prerequisites for success are improved access of low income countries to the markets of industrialised countries and the necessity to convince the ruling elites to sustain policy reform. Industrialised countries have hitherto neglected the political economy of decision-making in low income countries. Neither stricter conditionality nor more foreign aid or more sophisticated international commodity policies alone will be able to turn the tide. Policy reform has to be initiated from within low income countries with foreign donors mainly playing a catalytic role. For this reason, foreign aid policies should give priority to a strengthening of political bargaining processes within low income countries and to supporting actually implemented reform programmes. Such a foreign aid policy for the 1990s would require new criteria for aid allocation among countries and new priorities for aid programmes and projects. To remove politico-economic constraints and institutional weaknesses, foreign aid should focus on the development of a well-functioning domestic economic order, human resource development, and financing of poverty or ecology-related programmes. If some governments of low income countries are notoriously unwilling to improve fundamental economic conditions donors should not hesitate to reduce their efforts to the supply of emergency relief.
Keywords: 330; Entwicklungspolitik; Entwicklungshilfe; Entwicklungsländer